Effect of plasticizer type and concentration on tensile, thermal and barrier properties of biodegradable films based on sugar palm (Arenga pinnata) starch - Muhammed L. Sanyang; Salit M. Sapuan; Mohammad Jawaid; Mohamad R. Ishak; Sahari Japar (MDPI, 2015)
The use of starch based films as a potential alternative choice to petroleum derived plastics is imperative for environmental waste management. This study presents a new biopolymer (sugar palm starch) for the preparation of biodegradable packaging films using a solution casting technique. The effect of different plasticizer types (glycerol (G), sorbitol (S) and glycerol-sorbitol (GS) combination) with varying concentrations (0, 15, 30 and 45, w/w%) on the tensile, thermal and barrier properties of sugar palm starch (SPS) films was evaluated. Regardless of plasticizer types, the tensile strength of plasticized SPS films decreased, whereas their elongation at break (E%) increased as the plasticizer concentrations were raised. However, the E% for G and GS-plasticized films significantly decreased at a higher plasticizer concentration (45% w/w) due to the anti-plasticization effect of plasticizers. Change in plasticizer concentration showed an insignificant effect on the thermal properties of S-plasticized films. The glass transition temperature of SPS films slightly decreased as the plasticizer concentration increased from 15% to 45%. The plasticized films exhibited increased water vapor permeability values from 4.855 × 10−10 to 8.70 × 10−10 g·m−1·s−1·Pa−1, irrespective of plasticizer types. Overall, the current study manifested that plasticized sugar palm starch can be regarded as a promising biopolymer for biodegradable films.